Metachronous pancreatic cancer 18 years after resection of common bile duct cancer: A case report - Kim, Seoung Hoon (Frontiers in Surgery, 2022)
We report an extremely rare case of metachronous double cancers of the bile duct and pancreas in a single patient who underwent successful curative resections consecutively. At the age of 57, a woman underwent pylorus-preserving pancreaticoduodenectomy for a lesion that was pathologically diagnosed as moderately differentiated adenocarcinoma of the distal common bile duct. Eighteen years later, a pancreatic mass was detected during a follow-up examination. Abdominal computed tomography showed a bigger 2.3 cm lesion at the remnant pancreas body, which suggested a diagnosis of primary pancreatic cancer or metastasis. After admission and further work-up confirming no other lesions, completion total pancreatectomy was performed. The pathological diagnosis of the resected specimen was moderately differentiated pancreatic ductal adenocarcinoma, and this case highlights the occurrence of metachronous double primary cancers developed in both the distal bile duct and the pancreas with an interval of 18 years. This is the first report on the metachronous primary cancers of the bile duct and pancreas with a long interval within an English review of the literature in the MEDLINE. This case serves as another data point to guide surgeons that they should be vigilant for the postoperative long-term surveillance of patients with pancreatobiliary cancer.